Free proline accumulation in sugarcane under water restriction and spittlebug infestation Acúmulo de prolina em cana-de-açúcar sob estresse hídrico ou submetida ao ataque de cigarrinha-das-raízes - Eduardo Rossini Guimarães; Miguel Angelo Mutton; Márcia Justino Rossini Mutton; Maria Inês Tiraboschi Ferro; Gisele Cristina Ravaneli; Jorge Alberto da Silva (Scientia Agricola, 2008)
Mahanarva fimbriolata (Stål) (Hemiptera: Cercopidae) has become a key pest in the sugarcane (Saccharum officinarum) fields of center-south Brazil. Although some control technologies have shown to be efficient, the damage promoted by this spittlebug species and its interaction with sugarcane are poorly characterized. At high infestation levels the symptoms are similar to those of severe water restriction. This work was conducted to determine whether the stress promoted by spittlebug infestation can be measured in terms of free proline accumulation. The water restriction tolerance of two sugarcane genotypes was also compared. Two experiments were set up in a greenhouse and arranged in a completely randomized design in a 2 x 2 x 4 factorial, with two cultivars (SP80-1816 and RB72454), two stress levels (control and ten nymphs per plant or 50% water restriction), and four sampling dates. The water deficit caused by spittlebug nymphs sucking xylem sap does not result in proline accumulation, illustrating that there are different mechanisms to sense when the water deficit is caused by insect feeding or water potential variation in root cells. The cultivar RB72454 accumulates more free-proline, and the dry mass accumulation and stalk growth are less affected in this cultivar under water restriction. The levels of compatible solutes probably cannot be used to measure spittlebug infestation stress in sugarcane and RB72454 is more tolerant to water shortage than SP80-1816. A cigarrinha-das-raízes Mahanarva fimbriolata (Stål) (Hemiptera: Cercopidae) tornou-se uma praga importante da cultura da cana-de-açúcar na região centro-sul do Brasil. Estratégias de controle têm sido desenvolvidas, mas os danos promovidos por essa praga e sua interação com a cana-de-açúcar ainda são pouco caracterizados. Em altos níveis de infestação da praga, os sintomas nas plantas são muito semelhantes à restrição hídrica severa. Este trabalho foi conduzido com o objetivo de determinar se o estresse promovido pela infestação de ninfas de cigarrinha-das-raízes resulta em acúmulo de prolina livre, além de comparar dois genótipos de cana-de-açúcar quanto à tolerância ao déficit hídrico. Dois experimentos foram conduzidos em delineamento inteiramente casualizado, em esquema fatorial 2 x 2 x 4 com duas cultivares (SP80-1816 e RB72454), dois níveis de estresse (controle e dez ninfas por planta ou 50% de restrição hídrica) e quatro épocas. O déficit hídrico promovido por M. fimbriolata não resultou em acúmulo de prolina, ilustrando a existência de mecanismos distintos para a percepção do estresse hídrico promovido pela praga e pela variação no potencial osmótico nas células das raízes. A cultivar RB72454 acumula maiores teores de prolina livre, e o acúmulo de massa seca e o crescimento dos colmos são menos afetados nessa cultivar sob restrição hídrica. Os teores de solutos compatíveis provavelmente não podem ser utilizados para quantificar o estresse promovido por M. fimbriolata em cana-de-açúcar. A cultivar RB72454 é mais tolerante ao déficit hídrico do que a cultivar SP80-1816.